Business Advisory : a study on selected micro-sized SMEs in Kelantan , Malaysia - Mohd Nor Hakimin Yusof; Mohd Rafi Yaacob; Mohamed Dahlan Ibrahim (2010)
This study seeks to investigate the business advisory awareness among some micro-sized SMEs in Kelantan, Malaysia, focusing on the advisory services supplied by various government agencies. Micro-sized SMEs were the centre of the study because they represent a large number of SMEs in the country. Notwithstanding with the various advisory services provided by the government agencies in the state, result of the study showed the majority of respondents was not fully aware of and assured on the existence of business advisory services. Furthermore, the results of the study indicated no significant relationship between all the demographic factors of businesses and the level of awareness of business advisory among micro-sized SMEs. The key findings of the study are instructive. Actions should be taken by the government and its relevant agencies to enhance the level of awareness and knowledge of the importance of advisory among micro-sized SMEs. It seemed that the information pertaining to the business advisory services are not well disseminated to the targeted group. This failure distorts the government plan to efficiently support SMEs, thus leading to waste of scarce resources. Suggestions were also made to significantly address these issues